2022
DOI: 10.3390/ijms23052539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Injectable Biphasic Calcium Phosphate and a Bovine Xenograft in Socket Preservation: Qualitative and Quantitative Histologic Study in Humans

Abstract: This study is the first histologic evaluation of an injectable biphasic calcium phosphate (IBCP) in humans six months after socket preservation according to the principles of guided bone regeneration. After tooth extraction, the alveolar ridge of 21 patients was augmented with IBCP (maxresorb® inject) in the test group, while 20 patients in the control group received a bovine xenograft (BX) (cerabone®). Six months after augmentation, a reentry procedure was performed to collect biopsies of regenerated bone for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 62 publications
4
18
0
Order By: Relevance
“…[17][18][19][20] BCPs have been produced by mixing HA and β-TCP powders, or by sintering CDHAs at high temperature to produce mixtures of the two different phases, 20 and injectable BCP particles have been recently evaluated as bone graft materials for oral surgery applications. 21 BCP microspheres have been proposed for similar bone tissue regeneration. 22 Their shape and flowability make microspheres candidates as injectable materials, 23,24 and by controlling their porosity, BCP microspheres could be tailored for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] BCPs have been produced by mixing HA and β-TCP powders, or by sintering CDHAs at high temperature to produce mixtures of the two different phases, 20 and injectable BCP particles have been recently evaluated as bone graft materials for oral surgery applications. 21 BCP microspheres have been proposed for similar bone tissue regeneration. 22 Their shape and flowability make microspheres candidates as injectable materials, 23,24 and by controlling their porosity, BCP microspheres could be tailored for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio between the more soluble β‐TCP and the more stable HA can be varied to adjust the level of bioactivity, bioresorbability, osteoconductivity, and osteoinductivity 17–20 . BCPs have been produced by mixing HA and β‐TCP powders, or by sintering CDHAs at high temperature to produce mixtures of the two different phases, 20 and injectable BCP particles have been recently evaluated as bone graft materials for oral surgery applications 21 . BCP microspheres have been proposed for similar bone tissue regeneration 22 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there was lesser remaining grafting material (BCP 25.3%; DBBM 45.9%) and greater non-mineralized tissue (BCP 38.1%; DBBM 18.2%) in BCP than that in DBBM after 6 months of healing [14]. Another comparative study evaluated BCP and DBBM when used for socket preservation [15]. Histomorphometric analysis performed 6 months after the procedure showed no significant difference in new bone formation and residual materials between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, BCP has shown comparable favorable outcomes with deproteinized bovine bone mineral (DBBM), which is one of the most frequently used xenogeneic bone substitute materials [14,15]. A recent clinical study comparing histomorphometric outcomes of sinus floor elevation with BCP and DBBM demonstrated that the amount of new bone was similar between the two grafts (BCP 35.9%; DBBM 35.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation